THE EFFECT OF MOLECULAR WEIGHT ON THE THERMAL STABILITY OF CELLULOSE ACETATE - Zebua, Suniati; Zagoto, Nasrani; Halawa, Advent Tri Yanti; Zai, Liver Iman Putra; Purwandari, Vivi; Harahap, Mahyuni (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2024)
An organic ester with good mechanical characteristics (such as a high Young's modulus and tensile strength) is cellulose acetate (CA), a biobased polymer. Over the past few decades, the thermal characteristics of CA have been extensively studied. This study looked at the morphology and thermal characteristics of plasticized CA, particularly its mass loss according to thermogravimetric analysis. The analysis and comparison of the overall thermal behavior with theoretical models was done. The results of this study may have particular significance as certain polymers have a recognized dependence on β-relaxation for their mechanical attributes; this may also apply to CA.